Using Clinical and Multislice Computer Tomographic Features to Assess Temporomandibular Joint Osseous Involvement in Rheumatoid Arthritis: A Preliminary Study - Tamer GHEITA; Moushira DAHABA; Eman AHMED; Shorouk KHALIFA; Ayman BASMY3 (Archives of Rheumatology, 2012)
Objectives: In this study, we aimed to assess the osseous involvement of temporomandibular joint (TMJ) in rheumatoid arthritis (RA) patients by multislice computed tomography (MSCT) scanning with multiplanar reconstruction (MPR), and to find any relation to the clinical, laboratory and radiological disease parameters. Patients and methods: Twenty-four female patients (mean age 35.5±6.6 years; range 38.3 to 42 years) with definite diagnosis of RA were recruited in the study. Assessment was conducted through medical history, physical examination and clinical investigation. Disease Activity Scores in 28 Joints (DAS28) was calculated and Health Assessment Questionnaire-II (HAQ-II) used. The TMJs were assessed according to the TMJ clinical dysfunction score. Radiological grading of hands and feet was performed according to the modified Larsen score. Findings of the MSCT were assessed using the TMJ CT score. Results: Temporomandibular joint involvement was present in 70.83% of patients. The most commonly seen clinical TMJ dysfunction manifestations were difficult manipulation and pain, tenderness (45.83%) clicking (29.17%), locking (16.67%), followed by altered mouth opening (8.33%). The TMJ osseous involvement became more frequent (83.33%) after using bilateral MPR scan. The most frequent findings were mandibular condyle erosions, altered condyle position, mandibular subchondral sclerosis, articular eminence flattening, altered condyle shape and articular fossa erosion, osteophytes, articular eminence erosion, followed by mandibular subcondral cysts. The mouth opening was obviously reduced in 41.67% of patients. The TMJ CT score showed a trend to correlate with DAS28 and modified Larsen score. Conclusion: The MSCT MPR is a diagnostically reliable modality for the estimation of TMJ involvement in relation to the clinical manifestations and disease activity in RA patients. Early assessment is of utmost importance for the RA patients with symptomatic TMJ.